Mathematical models of hysteresis and their applications - Mayergoyz, I. D. (Elsevier series in electromagnetism., 2003)
This new edition has been significantly revised and updated to reflect advances in the field since the publication of the first edition, such as the systematic experimental testing of Preisach models of hysteresis. The author has, however, retained the two most salient features of the original, the emphasis on the universal nature of mathematical models of hysteresis and their applicability to the description of hysteresis phenomena in various areas of science, technology and economics and its accessibility to a broad audience of researchers, engineers, and students. Provides a unique emphasis on the development of universal mathematical models of hysteresis Accessibility to a broad audience, using simple and complex mathematical tools, application to various areas of science. Presents new theoretical and experimental results.